The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1186/s12958-018-0383-5
|View full text |Cite
|
Sign up to set email alerts
|

FMR1 expression in human granulosa cells increases with exon 1 CGG repeat length depending on ovarian reserve

Abstract: BackgroundFragile-X-Mental-Retardation-1- (FMR1)-gene is supposed to be a key gene for ovarian reserve and folliculogenesis. It contains in its 5’-UTR a triplet-base-repeat (CGG), that varies between 26 and 34 in general population. CGG-repeat-lengths with 55–200 repeats (pre-mutation = PM) show instable heredity with a tendency to increase and are associated with premature-ovarian-insufficiency or failure (POI/POF) in about 20%. FMR1-mRNA-expression in leucocytes and granulosa cells (GCs) increases with CGG-r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 36 publications
1
19
0
Order By: Relevance
“…GCs were recovered from the follicular fluid after transvaginal ultrasound-guided follicle puncture for in vitro fertilization (IVF), as described previously [17]. The follicles were aspirated with a specific needle (Premium Fas Single Lumen, #4551 NS-AS1; Gynétics Medical Products N.V., Lommel, Belgium) that was connected to a vacuum pump (Cook Medical, K-MAR-5200, Bloomington, IN, USA).…”
Section: Retrieval Of Granulosa Cellsmentioning
confidence: 99%
See 2 more Smart Citations
“…GCs were recovered from the follicular fluid after transvaginal ultrasound-guided follicle puncture for in vitro fertilization (IVF), as described previously [17]. The follicles were aspirated with a specific needle (Premium Fas Single Lumen, #4551 NS-AS1; Gynétics Medical Products N.V., Lommel, Belgium) that was connected to a vacuum pump (Cook Medical, K-MAR-5200, Bloomington, IN, USA).…”
Section: Retrieval Of Granulosa Cellsmentioning
confidence: 99%
“…GCs in RNAlater were centrifuged at 5000× g for 5 min, and the supernatants were removed. Total RNA was isolated from these GCs using TRIzol (Life Technologies by Thermo Fisher, Carlsbad, CA, USA) according to the manufacturer's instructions [38,39] with PEQGOLD PHA-SETRAP A 1.5 mL tubes (VWR International GmbH, Darmstadt, Germany) or MaXtract TM High Density 1.5 mL tubes (Qiage Germantown, MD, USA), as described previously [17]. RNA was dissolved in RNase-free water, and concentration and purity were determined using a NanoDrop 2000c UV-spectrometer (NanoDrop Products, Wilmington, DE, USA).…”
Section: Rna Extractionmentioning
confidence: 99%
See 1 more Smart Citation
“…The FMR1 gene contains a 5’-UTR triplet repeat (GGG) region, the length of which varies individually. It has been shown that FMR1 gene expression depends on the length and number of these triplet repeats [ 13 ]. Four allelic forms of the FMR1 gene are identified according to the number of GGG repeats (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The incidence of normal pure alleles (without interspersions) is low and their origin as well as the phenotypic impact in females, are still debatable. It has been proposed that "low zone" alleles, variably determined to be CGG ≤ 26 or CGG ≤ 23, are associated with different phenotypic outcomes (Mailick et al, 2014;Gleicher et al, 2015;Rehnitz et al, 2018). Some studies show that they are associated with decreased ovarian reserve and fertility issues, due to a mechanism not yet elucidated, possibly different from that involved in premutated alleles (Gleicher et al, 2015;Wang et al, 2017), although such negative effects were not corroborated by others (Spitzer et al, 2012;Ruth et al, 2016).…”
Section: Introductionmentioning
confidence: 99%